Pengaruh Kurs Dollar Amerika, Pendapatan Perkapita, dan Cadangan Devisa Terhadap Nilai Impor Kendaraan Bermotor di Indonesia - Indrawan, I Wayan Agus; Widanta, A.A Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Indonesia is a developing country where the industrial sector has not been able to meet all domestic demand, especially in commodity motor vehicle. Classical theory by David Ricardo stated that a country would benefit from international trade if the product specialization and exporting goods in which the country can produce relatively more productive as well, where the country's imported goods relatively less productive or unproductive, with this consideration, Indonesia entry in international trade. This study aimed to analyze the influence of the US dollar exchange rate, per capita income, and foreign exchange reserves, simultaneously and partially to the value of imports of motor vehicles in Indonesia in 1993-2013, and analysis techniques used are multiple linear regression analysis technique. The results of the data analysis F test showed that the US dollar exchange rate, per capita income, and foreign exchange reserves, an effect simultaneously to the value of imports of motor vehicles in Indonesia in 1993-2013. The result of partial test (t) which indicates, the US dollar exchange rate variable negative and not significant, variable Per Capita Income and Foreign Exchange Reserves positive and significant effect on imports of motor vehicles in Indonesia in 1993-2013.
Keywords: Motor Vehicles, Import, Rate, and Revenue